The covenant of water : a novel [large type] - Verghese, Abraham, 1955- (Thorndike Press large print top shelf, 2023)
"Spanning the years 1900 to 1977, The Covenant of Water is set in Kerala, on South India's Malabar Coast, and follows three generations of a family that suffers a peculiar affliction: in every generation, at least one person dies by drowning--and in Kerala, water is everywhere. At the turn of the century, a twelve-year-old girl from Kerala's long-existing Christian community, grieving the death of her father, is sent by boat to her wedding, where she will meet her forty-year-old husband for the first time. From this unforgettable new beginning, the young girl--and future matriarch, known as Big Ammachi--will witness unthinkable changes over the span of her extraordinary life, full of joy and triumph as well as hardship and loss, her faith and love the only constants. A shimmering evocation of a bygone India and of the passage of time itself, The Covenant of Water is a hymn to progress in medicine and to human understanding, and a humbling testament to the difficulties undergone by past generations for the sake of those alive today. It is one of the most masterful literary novels published in recent years"--